PROMOTION OF BASIL AS A TRADITIONAL HERB IN SERBIA - Beatović, Damir; Jelačić, Slavica; Moravčević, Đorđe; Zarić, Vlade (Economics of Agriculture, 2011)
Comprehensive feld research of Serbian basil have been performed, aimed promoting national and traditional herbs. Basil has been grown in Serbia in gardens since the 12th century. Due to its use in religious ceremonies it is grown on private plots and farms belonging to Serbian monasteries. Basil herb and essential oil are used in food and perfume industry and they are highly demanded raw material on the global market. A large number of samples have been collected during many years of research and documentation about basil originating from the territory of Serbia has been formed.